DENTAL GERM FORMATION AS INFLUENCED BY 5-FLUOROURACIL (5-FU) IN NEWBORN RATS - DA ROCHA, ROSILENE FERNANDES; BASTOS-RAMOS, WILMA P.; MATTOS FILHO, THALES ROCHA; NOGUEIRA, TEREZINHA O. (Archives of Veterinary Science, 1998)
Foi estudada a influência da droga antimitótica 5-fluoruracil (5-FU), administrada a ratas prenhes sobre a formação do germe dental de ratos recém nascidos. Foram utilizadas 125 fêmeas com 90-100 dias de idade e 15 machos adultos (Rattus rattus norvaegicus, albinus, Wistar). A droga foi injetada por via intraperitoneal a ratas grávidas, em doses únicas, aos 9º, 10º, 11º , 12º ou 13 º dias de gestação. Os animais foram divididos em quatro subgrupos de acordo com a dose administrada: 10, 20, 30 e 40 mg/kg. Os resultados mostraram que nessas doses, o 5-FU não teve efeito tóxico nas ratas prenhes, alem de perda de peso com doses mais elevadas (30-40 mg/kg), enquanto causou anomalias dentais nos embriões, bem como malformações externas. A proporção de tais anomalias foi, alem de dose dependente, influenciada pelo dia de gestação no qual antimitótico foi administrado às mães: foi observada maior sensibilidade ao 9º dia e menor ao 10º dia. Doses mais elevadas (30-40 mg/kg) causaram freqüentemente morte do embrião e reabsorção fetal. Agenesia do germe dentário foi freqüentemente observada. Abstract It was studied the influence of the antimitotic drug 5 - fluorouracil (5-FU), administered to pregnant rats, on dental germ formation of newborn rats. A total of 125 female aged 90-100 days and 15 male adult rats (Rattus rattus norvaegicus, albinus, Wistar) were used. The drug was injected intraperitoneally in single doses to females at the 9th, 10th, 11th, 12th and 13th days of pregnancy. The animals were divided in four groups according to the doses administered: 10, 20, 30 and 40 mg/kg. Results show that the drug induced no toxicity to mothers, other than loss of body weight with higher doses (30-40 mg/kg), but caused in the fetuses dental germ anomalies and body external malformations. The proportion of such anomalies were, besides dose dependent, influenced by the day of pregnancy when the drug was administered to the mothers: there was a greater sensitivity at the 9th day and a lesser one at the 10th day. Higher doses (30-40 mg/kg) caused frequently embryonic death or fetal uterine reabsorption. Agenesia of the dental germ was frequently found.